Productive efficiency by certification in the Brazilian's cowhide chain - Renófio, A. [UNESP]; Oliveira, J. A. [UNESP]; Alvarenga, R. P. [UNESP]; Queiroz, T. R. [UNESP] (My University, 2011)
The supply of Brazilian cowhide chain has, among other, the steps of land ownership and pasture formation, rearing, transportation, slaughterhouses and tanneries. In each of these steps occurs economic loss, social and environmental issues, which undermine the potential importance of leather in the national economic scene. You lose 60% of the quality standard required by the leather market in the first two stages and 15% in transportation and slaughterhouses. With regard to environmental matters, the livestock is regarded as responsible for about 50% of greenhouse gases into the atmosphere. In Brazil, the Middle West Region is the largest cattle rancher, because their conditions of occupation, still predominant, intense exploration of manpower for the sector. Aiming to contribute to solution of the informal character that exists in managing the domestic leather industry, the paper aims to present a proposal for the certification of the production chain of bovine cowhide from the structures already addressed by SISBOV. It appears that to make the proposal, there must be synergy among all stages of the chain and government commitment. The preparation of the article carried by the literature review related to issues of certification, and livestock production chain of bovine leather made in scientific congresses and national and international journals related to the areas of Administration, Engineering, Production and Agribusiness.
Keywords: Cowhide chain; Environmental impacts; Livestock cattle; SISBOV; Social impacts